2022
DOI: 10.25204/iktisad.971891
|View full text |Cite
|
Sign up to set email alerts
|

Dinî Yönelimin Finansal Davranışlar Üzerine Etkisi

Abstract: Bu çalışmanın amacı bireylerin dinî yönelim düzeylerinin finansal tutum ve davranışları üzerine etkisi hakkında literatüre katkı sunmaktır. Yapılan literatür taramasında, dinîn finansal davranışlar ile ilişkisi hakkında oldukça az araştırmaya rastlanmıştır. Bu nedenle literatüre katkı sağlamak amacıyla farklı yaş, eğitim, din ve gelir düzeylerinden oluşan 395 kişilik bir örneklem üzerinde araştırma yapılmıştır. İnternet üzerinden yapılan veri toplama yöntemi ile ankete katılanlardan 388'i değerlendirmeye alınm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The study by Sencer (1974) aims to analyze whether voters evaluate the past economic performance of the government while voting. In this study, it was found that voters cast their votes taking into account the past economic performance of the government before the election.…”
Section: Studies Related To Voter Behavior and Macro-economic Indicat...mentioning
confidence: 99%
“…The study by Sencer (1974) aims to analyze whether voters evaluate the past economic performance of the government while voting. In this study, it was found that voters cast their votes taking into account the past economic performance of the government before the election.…”
Section: Studies Related To Voter Behavior and Macro-economic Indicat...mentioning
confidence: 99%